2019
DOI: 10.1097/txd.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Portopulmonary Hypertension: A Survey of Practice Patterns and Provider Attitudes

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The 2017 survey of physicians at US liver transplant centers described in the Introduction found considerable heterogeneity in clinical practice and medications used to treat PoPH. 11 The authors concluded that this reflects how little is known about the optimal management of PoPH and called for more data from clinical trials and real-world experience to improve and standardize care. We believe that this need exists for all patients with PH and portal hypertension, not just those with PoPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2017 survey of physicians at US liver transplant centers described in the Introduction found considerable heterogeneity in clinical practice and medications used to treat PoPH. 11 The authors concluded that this reflects how little is known about the optimal management of PoPH and called for more data from clinical trials and real-world experience to improve and standardize care. We believe that this need exists for all patients with PH and portal hypertension, not just those with PoPH.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of 74 physicians at 35 liver transplant centers reported variability in provider attitudes and practice patterns across the US regarding PoPH management, highlighting the need to standardize care in patients with this dual comorbidity. 11 Understanding the current management and main cost drivers of portal hypertension in the setting of PH may identify strategies to improve quality of care. The objective of this study is to compare HCRU and costs between patients with portal hypertension and concomitant PH and patients with portal hypertension without PH.…”
mentioning
confidence: 99%
“…It is possible that awareness of the POPH MELD exception has grown and that transplant teams have become more comfortable with the criteria and overall application process. Furthermore, over the past 15 y, there has been increased appreciation for the complex relationship between POPH and LT among hepatologists and PH specialists‚ 13 as well as increased understanding of the role and potential benefit of LT in the management of POPH. 14 , 15 Additionally, the general increase in exception frequency over time may be related to the shifting epidemiology in etiology of cirrhosis seen in this cohort, specifically the decline in HCV, which is associated with a decreased risk of POPH, and increase in other causes‚ including NASH.…”
Section: Discussionmentioning
confidence: 99%
“…37,40,41,56 Because of inconsistent postoperative results, provider beliefs and attitudes on liver transplant in patients with POPH is far from unanimous, even among the experts in the field. A recent article by DuBrock et al 57 highlighted provider attitudes regarding POPH and liver transplantation at centers that performed > 50 transplants/year. The responses varied widely even among this select group (Figure 2).…”
Section: Prostacyclin Pathwaymentioning
confidence: 99%